Echovirus induces autophagy to promote viral replication via regulating mTOR/ULK1 signaling pathway - Wu, Chunchen; Zeng, Luzhi; Yi, Wenfu; Miao, Yuanjiu; Liu, Yihan; Wang, Qiming; Liu, Shi; Peng, Guoping; Zheng, Zhenhua; Xia, Jianbo (Frontiers in Immunology, 2023)
Among enteroviruses, echovirus can cause severe illnesses in neonates or infants, with high morbidity and mortality. Autophagy, a central component of host defense mechanisms, can function against diverse infections. In the present study, we investigated the interplay between echovirus and autophagy. We demonstrated that echovirus infection increases LC3-II expression dose-dependently, accompanied by an increased intracellular LC3 puncta level. In addition, echovirus infection induces the formation of autophagosome. These results suggest that echovirus infection induces autophagy machinery. Furthermore, phosphorylated mTOR and ULK1 were both decreased upon echovirus infection. In contrast, both levels of the vacuolar protein sorting 34 (VPS34) and Beclin-1, the downstream molecules which play essential roles in promoting the formation of autophagic vesicles, increased upon virus infection. These results imply that the signaling pathways involved in autophagosome formation were activated by echovirus infection. Moreover, induction of autophagy promotes echovirus replication and viral protein VP1 expression, while inhibition of autophagy impairs VP1 expression. Our findings suggest that autophagy can be induced by echovirus infection via regulating mTOR/ULK1 signaling pathway and exhibits a proviral function, revealing the potential role of autophagy in echovirus infection.